A Mixed-Methods Evaluation Framework for Electronic Health Records Usability Studies - Khairat, Saif (J Biomed Inform, 2019)
BACKGROUND: Poor EHR design adds further challenges, especially in the areas of order entry and information visualization, with a net effect of increased rates of incidents, accidents, and mortality in ICU settings. OBJECTIVE: The purpose of the study was to propose a novel, mixed-methods framework to understand EHR-related information overload by identifying and characterizing areas of suboptimal usability and clinician frustration within a vendor-based, provider-facing EHR interface. METHODS: A mixed-methods, live observational usability study was conducted at a single, large, tertiary academic medical center in the Southeastern US utilizing a commercial, vendor based EHR. Physicians were asked to complete usability patient cases, provide responses to three surveys, and participant in a semi-structured interview. RESULTS: Of the 25 enrolled ICU physician participants, there were 5(20%) attending physicians, 9 (36%) fellows, and 11 (44%) residents; 52% of participants were females. A significant negative correlation was found between EHR usability and ease of use with frustration, such that as usability and ease of use increased, frustration levels decreased (p=.00 and p=. 01 respectively). Performance was negatively correlated with complexity and inconsistency in the interface design, where the higher degrees of complexity or inconsistency in the EHR associated to lower perceived performance of physicians (p=.03 and p=.00 respectively). DISCUSSION: Physicians remain frustrated with the EHR due to difficulty in finding patient information. EHR usability remains a critical challenge in healthcare, with implications for medical errors, patient safety, and clinician burnout. There is a need for scientific findings on current information needs and ways to improve EHR-related information overload.